2011
DOI: 10.4081/cp.2011.e57
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine for an Awake Fiber-Optic Intubation of a Parturient with Klippel-Feil Syndrome, Type I Arnold Chiari Malformation and Status Post Released Tethered Spinal Cord Presenting for Repeat Cesarean Section

Abstract: Patients with Klippel-Feil Syndrome (KFS) have congenital fusion of their cervical vertebrae due to a failure in the normal segmentation of the cervical vertebrae during the early weeks of gestation and also have myriad of other associated anomalies. Because of limited neck mobility, airway management in these patients can be a challenge for the anesthesiologist. We describe a unique case in which a dexmedetomidine infusion was used as sedation for an awake fiber-optic intubation in a parturient with Klippel-F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…The antisialagogue and moderate analgesic properties of dexmedetomidine have been cited as other advantages. 41,42 We identified 19 articles, five RCTs 13,29,43-45 and 14 case reports and case series [46][47][48][49][50][51][52][53][54][55][56][57][58][59] describing the use of dexmedetomidine for AFOI, usually as the sole agent but occasionally in combination with midazolam 43 or ketamine. 60 Although a TCI system for dexmedetomidine has been described for awake intubation, 47 it is generally administered as a slow bolus (usually 1 lgÁkg -1 over 10-20 min) to avoid peak-dose hypertension (which may exacerbate a bradycardia-related fall in cardiac output) followed by an infusion (usually of 0.1-0.7 lgÁkg…”
Section: Dexmedetomidinementioning
confidence: 99%
See 1 more Smart Citation
“…The antisialagogue and moderate analgesic properties of dexmedetomidine have been cited as other advantages. 41,42 We identified 19 articles, five RCTs 13,29,43-45 and 14 case reports and case series [46][47][48][49][50][51][52][53][54][55][56][57][58][59] describing the use of dexmedetomidine for AFOI, usually as the sole agent but occasionally in combination with midazolam 43 or ketamine. 60 Although a TCI system for dexmedetomidine has been described for awake intubation, 47 it is generally administered as a slow bolus (usually 1 lgÁkg -1 over 10-20 min) to avoid peak-dose hypertension (which may exacerbate a bradycardia-related fall in cardiac output) followed by an infusion (usually of 0.1-0.7 lgÁkg…”
Section: Dexmedetomidinementioning
confidence: 99%
“…51 The safe respiratory profile of dexmedetomidine has been borne out by reports describing its use in patients with raised intracranial pressure at risk from hypoventilation 52 and in obstetrics with minimal adverse neonatal sequelae. 53,54 The ability to produce a deeply sedated state while maintaining a safe degree of respiratory function has also allowed it to be successfully used in children and uncooperative adults. 55,56 Nevertheless, the real advantage of a sedative that spares respiratory function may become apparent when the clinician is presented with patients already in or at risk of airway obstruction and/or respiratory failure; yet (not surprisingly), to date, there have been only limited case series dealing with such cases.…”
mentioning
confidence: 99%
“…Successful use of dexmedetomidine for labor analgesia and/or cesarean section under general anesthesia have been reported in several case reports, if neuraxial anesthesia was contraindicated [ 12 ], if the patient refused neuraxial anesthesia [ 13 ], or as an adjunct to intravenous opioid-based analgesia if pain relief was not satisfactory [ 14 , 15 ]. Dexmedetomidine sedation for awake fiberoptic intubation was successfully used in a parturient with spinal muscular atrophy for cesarean delivery [ 16 ] and in a parturient with Klippel-Feil syndrome [ 17 ]. El-Tahan et al [ 18 ] recently showed that preoperative administration of dexmedetomidine at a dose of 0.4–0.6 μg/kg/h over 20 min attenuates maternal hemodynamics and hormonal response to cesarean section without adverse neonatal effects.…”
Section: Introductionmentioning
confidence: 99%
“…Shah and co-workers [20] used dexmedetomidine (a loading dose of 1 lg kg À1 over 10 min followed by a maintenance infusion at 0.7 lg kg À1 h À1 ) as sedative during awake fiberoptic intubation in pregnant female with history of Klippel-Feil Syndrome with congenital fusion of their cervical vertebrae posted for caesarean section. Toyama and colleagues [21] used dexmedetomidine for attenuation of hemodynamic response during induction and emergence of general anesthesia in pregnant female 32 weeks' gestation with history of primary pulmonary hypertension during caesarean section.…”
Section: Discussionmentioning
confidence: 99%
“…Dexmedetomidine was used in previous studies in human during caesarean section and for labour analgesia without any harmful effect on the neonatal outcome [18][19][20][21]34,35].…”
Section: Dexmedetomidine Groupmentioning
confidence: 99%